THE EFFECTIVENESS OF JSJ (JIN SHIN JYUTSU) IN ADDRESSING EMESIS OF GRAVIDARUM IN PREGNANT WOMEN AT PMB IKA MARDIYANTI SIDOARJO - Ika Mardiyanti; Nur Zuwariyah (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Nausea and vomiting are often ignored because they are considered as a normal consequence at the beginning of pregnancy without knowing the great impact they can cause. The incidence of nausea and vomiting occurs in 60-80% primigravida and 40-60% multigravida. If nausea and vomiting in pregnant women is not immediately carried out further action causes pregnant women to be malnourished so that the fetus does not get adequate nutrition and can have an impact on the fetus it contains.Objective: This study aimed to determine the effect of JSJ massage (Jin Shin Jyutsu) on Emesis Gravidarum on pregnant women in PMB Ika Mardiyanti, Jedong Cangkring Village, Prambon Sub-District, Sidoarjo District, East Java Province, Indonesia.Method: This study used an observational analytic design with a cross sectional approach. The sample in this study was taken by consecutive sampling. The method of collecting data uses primary data, by applying JSJ Massages (Jin Shin Jyutsu) and performing anamnesas against emesis gravidarum experienced by pregnant women. Data analysis using McNemar Test and Mann Withney U Test.Results: The results showed that respondents aged low risk (20-35 years) were 20 respondents (66.66%); had good nutritional status (LILA> 23.5 cm); as many as 25 respondents (83.33%); and had low risk parity (children <5), as many as 21 respondents (70.00%). Statistical analysis with McNemar Test obtained ρ = 0.125> α = 0.05, meaning that there was no effect of JSJ massage on emesis gravidarum. The Mann Withney U Test results obtained ρ = 0.217> α = 0.05, meaning there is no difference between the intervention group and the control group.Conclusion: The results showed that there was no effect of giving JSJ massage to emesis gravidarum in pregnant women. It is expected that midwives will increase information and education communication (IEC) about the handling of emesis gravidarum both pharmacologically and non-pharmacologically so as not to become pathological and have an impact on the mother and the fetus. Keywords: Massage Jin Shin Jyutsu (JSJ), emesis gravidarum, pregnant women.